The University’s Impact of Organizational Support on Competency of Academics - Yao, Jiang; Keat, Ooi Boon (Economics & Management Review, 2024)
Amidst a complex and challenging developmental landscape, academics have undergo profound transformations in their identity, status and responsibilities. In this context, competencies have emerged as central in discussions regarding educational policies and professional development for academics. Competency development is integral to the growth of the academics professionals, encompassing teaching competence, research competence, communication and collaboration competence and personal characteristics competence. The development of competency is not only the manifestation of personal and professional development, but also a contribution to the overall quality of education, research, and academic reputation of the university. This paper explores the significance of organizational support for academics’ competencies.